Het Amsterdamse fabrieksambt van 1595-1625 (Bulletin KNOB, 1994)
The fact that architecture in the Northern Netherlands was flourishing in the early 17th century, at the moment when the war against Spain was taking a favourable turn, manifested itself most clearly in Amsterdam. The building trade of this rapidly growing town ('stadsfabrieksambt' / public works) was expanding. Everything that the town wished to be built was designed and made by public works. In 1595 its leadership was renewed, Hendrick Jacobsz Staets was appointed town carpenter, Cornelis Danckertsz town bricklayer and Hendrick de Keyser (1565-1621) town mason and sculptor.As the archives of public works were lost, little is known about the cooperation between these three. Too many ill-founded contemplations have been devoted to the assumed bad relationship between Staets and De Keyser. However, gradually we have learned more about Hendrick de Keyser's private work for other towns and for private persons. We have compared this private work with the many small buildings the town had built between 1600 and 1621. It proves to form a unity with these.It seems likely that Staets initially also designed buildings - which was customary for a town carpenter - and called in De Keyser for the decorative work. After approximately 1605, however, De Keyser designed all new construction for the town. His work shows a personal use and an autonomous development of the motifs of Architectura Moderna (1577) of Hans Vredeman de Vries. The major aspects he derived from it are the differences in design of each floor, the window coverings which were incorporated into the main frames separating the floors, and the enlivenment of the wall sections by means of niches or chinks.Around 1610 Hendrick De Keyser's style was getting more mature. The small natural-stone blocks in the window arches made way for a few larger blocks. Thus a new fashion in the architecture of facades started. He also experimented with triangular arches after the model of the Porta Pia by Michelangelo. The many interruptions in the cornices made his work a typical example of Dutch Mannerism.On the other hand, his work also reveals pre-Classicist characteristics. And in this, too, he follows the work of Vredeman de Vries. Nowadays the latter is too often regarded as a source of inspiration for incoherent gables, in spite of the fact that among his examples there are more buildings with hipped roofs than with gables.The oldest pre-Classicist building in Amsterdam was the weighhouse at Dam square, dating back to 1563. From that moment on buildings with Classicist and Mannerist characteristics arose in the town. Until after 1630 Jacob van Campen and Philips Vingboons definitely guided architecture into the direction of Classicism.